Educational leadership global contexts and international comparisons - Wiseman, Alexander W., 1968- (International perspectives on education and society, 2009)
This volume of "International Perspectives on Education and Society" investigates the changing face of educational leadership from comparative and international perspectives. Various definitions of leadership have transformed the way that educators around the world think about teaching, administration, and policy in recent years. Yet, there is relatively little known about how educational leadership works in many specific systems, cultures and societies around the world. And, much of the published research and literature on educational leadership focuses on only a handful of countries and cultures even though empirical research suggests that leadership is differently contextualized by society, culture, and organizational environment. The chapters in this volume ask and answer two main questions: What is the difference between theoretical definitions of leadership and what works in different systems, cultures, and societies around the world? And, more importantly, how are both ideas about and evidence of educational leadership either the same or different across different national and cultural contexts?